Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2319510x19848857
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Farmers’ Intention to Adopt Sustainable Agricultural Practices

Abstract: The present research aims to study the farmers' intention to adopt sustainable agriculture practices. The sample size of 283 respondents has been considered and responses have been recorded from different areas of Punjab state (India) using a research schedule. The study considered six dimensions namely perceived usefulness; self efficacy; extension services; social capital; facilitating conditions and compatibility have been taken from the existing literature. The data thus collected, has been analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 69 publications
(161 reference statements)
0
16
0
Order By: Relevance
“…It is found that all the values are above the threshold level of fit indices. Results show that the degree of freedom = 2.196; CMIN/df = 549.111; Goodness of fit index = 0.923 reflects good model fit, adjusted goodness of fit index = 0.900; Tucker–Lewis index = 0.971; normal fit index = 0.956; root means square error of approximation (RMSEA) = 0.048; and comparative fit index = 0.976 (Table 4) are below the conservative cut-off values (Syan et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is found that all the values are above the threshold level of fit indices. Results show that the degree of freedom = 2.196; CMIN/df = 549.111; Goodness of fit index = 0.923 reflects good model fit, adjusted goodness of fit index = 0.900; Tucker–Lewis index = 0.971; normal fit index = 0.956; root means square error of approximation (RMSEA) = 0.048; and comparative fit index = 0.976 (Table 4) are below the conservative cut-off values (Syan et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Kaiser–Meyer–Olkin (KMO) and Bartlett’s test of sphericity were also used to check the suitability, and results were satisfactory to proceed further (Table 2). To check the reliability, Cronbach’s α was calculated (0.724), which was assumed to be satisfactory for behavioural studies (Cronbach, 1951; Hundal & Kumar, 2015; Syan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, six academicians (two experts each from the field of marketing, advertising, and sustainable development) and two industry experts were consulted for making the construct and scale more effective. The survey tool was tested through a pilot study of 130 respondents' and the needed changes were made on the final scale according to the recommendations (Hair et al, 2015; Syan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The instrument for this study was based on the Technology Acceptance Model (TAM), which has been frequently used in technologyacceptance studies. Seven variables (predictive factors) were included in the framework, namely perceived benefits and risks (Amin et al, 2014), perceived selfefficacy (Hosseini et al, 2016;Syan et al, 2019), perceived fit (lau and Phau, 2006;Volckner and Sattler et al, 2006), perceived cost (Mwangi and Kariuki, 2015), government support, and market demand (Deng et al, 2019). it was hypothesized that these influence farmers' attitudes to the adoption of GM crops (see Figure 1).…”
Section: Research Conceptual Frameworkmentioning
confidence: 99%